A critical appreciation of AI-Tayyeb Salih's novel: seasons of migration to the north / Tengku Intan Suzila Tengku Sharif and Mohd Yusri Mohamad Noor - Tengku Sharif, Tengku Intan Suzila; Mohamad Noor, Mohd Yusri (2016)
This novel is about a human crossroad between the East and the West culture. AI-Tayyeb Salih's Seasons of Migration to the North is an interesting novel that can be analyzed from several points of view. This is a convenient sampling, which suits the theme of Islamization and cultural adaptation. The focus of this paper are firstly religion and assimilation; and secondly, culture and adaptation. The central character - Mustaffa Sa'eed's development and growth are set under the microscope for analysis. Thus, the appearance of the matters are coded accordingly. Each coding is then elaborated. A discourse analysis enables the growth of character to be discussed. Firstly, findings suggest that one's ability to adapt to change while adhering to faith is vital. Secondly, challenges in life are always lurking to test one's faith. In short, this paper will suggest that faith is significant in promoting assimilation and adaptation to cultural and religious challenging environment.